The Influence of Leadership Style and Work Environment on Employee Performance - Rahmawati, Putri Pramudia; Setyowati, Rini (Review: Journal of Multidisciplinary in Social Sciences, 2025)
One way to achieve optimal employee performance or even improve it is to create a comfortable, safe, conducive, and pleasant work environment. This study uses a quantitative design. The data collected from the questionnaire will be analyzed using statistical tools with the help of SPSS. Based on the analysis, it can be found that there is an influence of leadership style , performance environment, simultaneously on employee performance. Based on the results of the analysis, it can be seen that there is a significant influence between leadership style, on employee performance Based on the data that has been presented previously, it shows that the work environment variable has a positive effect on employee performance.